2013
DOI: 10.1111/jomf.12042
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity, Attitudes, and Living With Parents During Young Adulthood

Abstract: Race/Ethnicity, Attitudes, and Living With ParentsDuring Young Adulthood Non-White young adults are more likely to live with their parents throughout their 20s, more likely to return home after going away to college, and less likely to leave again after returning. Scholars have speculated that subcultural differences in attitudes toward marriage and family play a key role in generating racial/ethnic differences in rates of coresidence with parents among young adults. Data from the National Education Longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 43 publications
2
46
0
1
Order By: Relevance
“…For instance, with only one exception students who lived at home reported doing so due to financial constraints and not personal or cultural preference. Similar here is Britton (2013), whose longitudinal study of youth from eighth grade through the age of 26 of found that attitudes toward family did not explain racial/ethnic variation in rates of co-residence.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…For instance, with only one exception students who lived at home reported doing so due to financial constraints and not personal or cultural preference. Similar here is Britton (2013), whose longitudinal study of youth from eighth grade through the age of 26 of found that attitudes toward family did not explain racial/ethnic variation in rates of co-residence.…”
Section: Discussionsupporting
confidence: 69%
“…This influence is especially likely among college-attending emerging adults who do not leave home, but live with or near family throughout their young adulthood. In fact, co-residers comprise a substantial and perhaps growing proportion of students enrolled in institutions of higher education in the U.S., which makes the study of family relationships and their impact on emerging adult development an important area of study (Britton 2013;Pew Research Center 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of racial/ethnic differences in the transition to adulthood often ignore immigrant status, largely because few data sets contain sufficient samples of first-and second-generation immigrant youth (for exceptions, see Britton 2013; Treas and Batalova 2011). It is important not to conflate immigrant and racial/ethnic differences.…”
Section: Intergenerational Relationships In Immigrant and Minority Famentioning
confidence: 99%
“…Middle-age and older parents often help with housing. Growing numbers of adult children, especially sons and non-Whites, are living with their parents (Britton, 2013;Marshall, 2011;Roberts, 2013). Terms like "boomerang kids," the "crowded nest," and the "refilled nest" are now familiar, reflecting how common this trend has become.…”
Section: Intergenerational Ties: Inside Familiesmentioning
confidence: 99%